En face optical coherence tomography detection of Schlemm’s canal in primary open angle glaucoma - Huang, Haili; Tian, Lijia; Sun, Xinghuai; Chen, Yuhong (Frontiers in Physiology, 2023)
Purpose: To compare the morphological characteristics of Schlemm's canal (SC) in patients with primary open-angle glaucoma (POAG) and healthy controls, using swept-source optical coherence tomography (SS-OCT) with en face reconstruction. Methods: In this Prospective comparative study, we included 100 eyes from 50 patients diagnosed with POAG and 50 healthy controls. Three-dimensional cube and line scans of the temporal and nasal quadrants of the anterior segment of the limbus were acquired using SS-OCT. SC was identified using en face and cross-sectional images. The diameter and area of SC in cross-sectional images and the visible percentage and area of SC in en face images were measured using ImageJ. Results: SC was observed in 84% of en face images and 81% of cross-sectional images in eyes with POAG but in 92% of en face images and 86% of cross-sectional images in control eyes. Significant differences between the POAG and normal control eyes were found in the en face area (0.35±0.14 mm2 vs. 0.56±0.22 mm2 in the temporal quadrant and 0.36±0.14 mm2 vs. 0.58±0.23 mm2 in the nasal quadrant; both P0.001) and visible percentage of SC (85.71% vs. 94.91% and 87.10% vs. 95.52% in the temporal and nasal quadrant respectively , both P0.001) in en face images as well as the cross-sectional area (2790.9±942.2 μm2 vs. 4138.6±2027.8 μm2 in the temporal quadrant and 2805.7±947.2 μm2 vs. 4224.0±2002.2 μm2 in the nasal quadrant, both P0.001) and diameter of SC (123.1±25.4 μm vs. 149.5±34.7 μm in the temporal quadrant and 126.3±28.9 μm vs. 155.3±36.0 μm in the nasal quadrant, both P0.001) in cross-section images. In addition, the mean intraocular pressure (IOP) significantly correlated with the en face area, visible percentage of SC, and cross-sectional area in the temporal and nasal quadrants. Conclusions: SS-OCT can obtain high-quality en face images of SC without post-acquisition processing. Eyes with POAG had a decreased en face SC area compared with normal eyes. A correlation between SC area, visible percentage of en face images, and IOP was also observed.